A Survey on Dispersion Management Using Optical Solitons in Optical Communication System. (2016) - Nagesh, Revathy; Rajesh Mohan, R.; Asha, R.S.
Abstract: In this paper, the dispersion management in optical communication systems using soliton transmission technique is studied. An optical soliton is a special kind of light pulse that can be transmitted over fibre optic channel due to the exact compensation between nonlinearity and linear broadening due to group velocity dispersion. Since the soliton data looks the same at different distances along the transmission, this technique can be used to overcome the data transmission limitations in Radio over Fibre (RoF) communication systems. This paper investigates the concepts of dispersion management using solitons in optical fibre. It analyses the system with and without soliton parameters in terms of Q-factor, pulse broadening and eye diagram. From the simulation results, it is found that the Q-factor is improved by 77.9751 dB for the soliton system. The results show that the pulse broadening is less in the output spectrum of dispersion managed system. The eye diagrams also show that the noise is minimal for the system with soliton. The results show that the performance of dispersion managed system with soliton is good.